3D Modeling and Simulation of Electrohydrodynamic Ion-Drag Micropump with Different Configurations of Collector Electrode - Shakeel Ahmed, Kamboh; Jane, Labadin; Andrew Ragai Henry, Rigit (2012)
This paper presents 3D simulation work for iondrag micropump. The commercial simulation software Comsol Multiphysics 4.2 was used to model and simulate ion-drag micropump for three different configurations of collector electrode. The purpose of the simulation was to investigate the ways to improve the performance of the micropump and analyze the effect of the electric field, fluid velocity and pressure gradient on the different design of the micropump. The initial simulation patterns reveal the behavior of the electric field, fluid velocity and pressure gradient in the domain of each of the design of the micropump. From the simulation results it is observed that at the top of the flow channel the fluid flow and pressure field is low because the driving electric body force is stronger near the electrodes surface and weaker at the top regions of the microchannel.